2017
DOI: 10.1523/jneurosci.1929-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structure and Function Associated with Younger Adults in Growth Hormone Receptor-Deficient Humans

Abstract: Growth hormone receptor deficiency (GHRD) results in short stature, enhanced insulin sensitivity, and low circulating levels of insulin and insulin-like growth factor 1 (IGF-1). Previous studies in mice and humans suggested that GHRD has protective effects against age-related diseases, including cancer and diabetes. Whereas GHRD mice show improved age-dependent cognitive performance, the effect of GHRD on human cognition remains unknown. Using MRI, we compared brain structure, function, and connectivity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 57 publications
2
31
0
1
Order By: Relevance
“…32 Although the age-related decline in the activity of the growth hormone-IGF-1 axis is considered to contribute to age-related changes that are similar to those observed in growth hormone-deficient adults, growth hormone–IGF-1 deficiency or resistance is also known to result in prolonged life expectancy, at least in animals. 3335 These data raise the question of whether or not growth hormone deficiency constitutes a beneficial adaptation to ageing, and therefore requires no therapy. Moreover, although growth hormone therapy has been shown to exert positive effects on growth hormone-deficient patients, its safety, efficacy, and role in healthy older individuals is highly controversial.…”
Section: Hypothalamic–pituitary–peripheral Organ Axesmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Although the age-related decline in the activity of the growth hormone-IGF-1 axis is considered to contribute to age-related changes that are similar to those observed in growth hormone-deficient adults, growth hormone–IGF-1 deficiency or resistance is also known to result in prolonged life expectancy, at least in animals. 3335 These data raise the question of whether or not growth hormone deficiency constitutes a beneficial adaptation to ageing, and therefore requires no therapy. Moreover, although growth hormone therapy has been shown to exert positive effects on growth hormone-deficient patients, its safety, efficacy, and role in healthy older individuals is highly controversial.…”
Section: Hypothalamic–pituitary–peripheral Organ Axesmentioning
confidence: 99%
“…33 Further investigation could lead to an improved understanding of the mechanisms underlying these differences in brain structure and function, and could contribute to the identification of treatments for age-related cognitive deficits. This observation raises the possibility that growth hormone receptor inhibition has the potential to protect against age-dependent cognitive decline.…”
Section: Hypothalamic–pituitary–peripheral Organ Axesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently a small study with 12 members of the Ecuadorian cohort of LS patients reported that they performed significantly better in memory tasks and had significantly lower cognitive impairment compared to their unaffected relatives (273). In human acromegaly patients, recent studies have reported cognition deficits, decreased short-term and long-term memory, anxiety and impaired decision making, and decreased activities in pre-frontal and mid-temporal cortices in brain (274,275,276,277).…”
Section: Cognitive Studies In Humans With Ghr Deficiencymentioning
confidence: 99%
“…The height of children is rapidly becoming a social issue as there is an increase in the number of people who are concerned about their child's height. As a result, GH therapy is being indiscriminately used without adequate protection against side effects [38][39][40][41][42][43][44][45][46][47]. This study investigated the beneficial effect of using spirulina as a dietary supplement on skeletal growth and growth-related hormone levels in growing male rats.…”
Section: Introductionmentioning
confidence: 99%